PERGESERAN SUMBER EPISTEMIK DALAM PEMBELAJARAN MATEMATIKA DI ERA ARTICIAL INTELLIGENCE (AI): LITERATURE REVIEW TERHADAP TRANSFORMASI PEMAHAMAN KONSEPTUAL SISWA: Pergeseran Sumber Epistemik Dalam Pembelajaran Matematika Di Era AI: Tinjauan Sistematis Pemahaman Konseptual Siswa - Aksa, Intan; Ailda; Hardini, Citra; Ainia Hasri, Nurul; Ikhwan, Muhammad (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2026)
This study aims to systematically examine the shift in epistemic sources in mathematics learning during the era of artificial intelligence (AI) and its implications for students' conceptual understanding. It employs a systematic literature review approach guided by the PRISMA framework, searching databases such as ScienceDirect, SpringerLink, Google Scholar, DOAJ, and Garuda, which yielded 20 selected articles published between 2018-2026, analyzed via thematic synthesis to identify key patterns. Findings reveal a transformation of epistemic sources from traditional teacher and textbook models to an interactive, adaptive AI-driven digital ecosystem that mediates knowledge through visualization, personalization, and feedback—yet poses challenges like potential technology dependence that may reduce the depth of conceptual thinking. Main themes include shifts in knowledge authority, AI's role as a cognitive mediator, and pedagogical implications such as the teacher's facilitative role. The study emphasizes balanced Artificial Intelligence (AI) integration to support deep conceptual understanding in the digital age.